PEMANFAATAN LIMBAH BATUBATA MERAH DALAM MENINGKATAN DAYA DUKUNG TANAH LEMPUNG - Herman Herman; Mia A Mia A (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Clay soil is a soil that causes a lot of problems, has low permeability and is difficult to handle in the field. The grains are very fine and composed of minerals that can be affected by water. If the water content is high this soil expands and its strength decreases significantly and causes damage to the structure above it. To overcome this problem, researchers tried to use brick waste as a mixing material, because this material is very commonly found in the field. The composition of the waste bricks in the soil content is 0%, 10%, 15% and 20%, the tests carried out include the Atterberg test, grain size analysis, and compaction test. For the CBR test and free compression test carried out at the maximum solid condition. Tests were carried out both on soil samples and on soil samples that had been mixed with brick waste. The test results show that the waste bricks in the soil can reduce soil plasticity, it can be seen by the decrease in the liquid limit value (LL), plasticity index (PI) and the free compressive value (qu) of the soil. While soil density, CBR (soaked, unsoaked) initially increases, as the percentage of waste bricks in the soil content increases, these values decrease. The best results were achieved at 15% of the waste bricks in the soil content.